Carboplatin chemotherapy in a pregnant patient with undifferentiated ovarian carcinoma: case report and review of the literature. Issue 1 (1st January 2008) - Tabata, T.; Nishiura, K.; Tanida, K.; Kondo, E.; Okugawa, T.; Sagawa, N.
Abstract : There are already 12 reports of women treated by chemotherapy for epithelial ovarian cancer during pregnancy. However, most cases received chemotherapy of single cisplatin or cisplatin-based regime, and only four cases received carboplatin-containing chemotherapy. We report the case of a woman treated with single-agent carboplatin during pregnancy. The patient underwent bilateral salpingo-oophorectomy at 18 weeks of gestation and was diagnosed as having stage IC undifferentiated ovarian carcinoma. She was treated with four courses of carboplatin (area under the curve = 6.0) chemotherapy during pregnancy without severe toxicity. At 33 weeks of gestation, cesarean section was performed, followed by total hysterectomy, omentectomy, and pelvic and para-aortic lymphadenectomy. No residual disease was histologically shown. The patient underwent additional chemotherapy with carboplatin and paclitaxel. After one year of follow-up, the baby shows normal growth and the patient has no evidence of disease. Postponing the termination of pregnancy by single-agent carboplatin chemotherapy during pregnancy might be considered as an option for therapy in selected women with ovarian malignancies.